Tick-Borne Encephalitis – epidemiological analysis of case count and prevention from 2007-2017 - Ruszel, Kinga; Pokorski, Piotr; Winiarz, Aleksandra; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2019)
The following article presents the epidemiological situation in Poland over the 2007-2017 period. The article is based on the analysis of “Contagious diseases and toxoinfections in Poland” and “Vaccination in Poland” surveys and pamphlets from the State Department of Hygiene. Supplementary information concern infection by the virus, clinical manifestation, detection, diagnostic procedure and vaccination against TBE virus. The results were developed using a descriptive method.Tick-borne encephalitis (TBE) is a serious disease of the central nervous system that can occur in many clinical forms. In Poland, TBE is the main cause of brain inflammation of viral etiology. The diseases are characterized by seasonality and occur mainly in the spring and summer. The highest number of cases occurred in 2010, and the lowest in 2015. In 2015/2016, the number of cases with TBE increased almost twice. It was at the same level in 2017. Every year the highest number of TBE cases is recorded in the region Podlasie and it accounts for about 80% of cases of TBE in Poland. There is no causative treatment of TBE, the only form of prevention of the disease are protective vaccinations, which in Poland are recommended for specific groups of people. Analysis of TBE vaccination data has shown a gradual increase in the interest in TBE protective vaccinations from 2014 to 2017. Despite the growing number of people vaccinated against TBE in Poland, the number of cases remains high. The society in TBE prophylaxis should be educated.